The origins, prevention and treatment of infant crying and sleeping problems : an evidence-based guide for healthcare professionals and the families they support - St. James-Roberts, Ian (Hove, East Sussex : Routledge, 2012)
'Babies who cry a lot, or are unsettled in the night, are common sources of concern for parents and, consequently, costly problems for health services. In this book, Ian St James-Roberts summarises new evidence concerning infant crying and sleeping problems to provide an evidence-based approach to the subject. The book begins by distinguishing between infant and parental parts of the problems and provides guidelines for assessing each issue. Topics covered include: - the pros and cons of'infant-demand' versus'limit-setting' - causes of infant'colicky' crying and night waking - effects of night-time separations on infant attachments - interventions such as swaddling and herbal remedies. Since there is now firm evidence that parents' vulnerabilities and cultural backgrounds affect how problems are defined and guidance is acted upon, and that parents who wish to do so can reduce infant crying and unsettled night waking, social factors are considered alongside medical issues. Translating research evidence into practical tools and guidance, The Origins, Prevention and Treatment of Infant Crying and Sleeping Problems will therefore be essential reading for a wide range of professionals including mental health staff, social workers, midwives and health visitors'--
Includes bibliographical references and index.
Keywords: Sleep disorders in children; Infants -- Sleep; Crying in infants; Sleep disorders in children -- Treatment; Parent and child